HER+ Research Collection. Explore the latest research and innovation on gender and climate change - Awinoh, Martha; Tabassum. Sumaya; Lecoutere, Els (CGIAR System Organization, 2024)
Welcome to CGIAR Gender Equality Initiative, HER+ research collection. Here you’ll find a curated collection of the latest publications and innovations from HER+ initiative TRANSFORM, EMPOWER, PROTECT, and VOICE work packages. Simply click on the titles, hyperlinks, and buttons and dive into our latest publications, high-level initiative outputs, and work package progress and achievements. The exclusive ready-to-use tools and metrics button offers innovation solutions to addresses both systemic and individual constraints that hinder gender equality and climate resilience in food, land and water systems. Stay connected with our regularly updated gender research evidence, designed to accelerate progress towards more equitable, inclusive, and climate resilient agrifood systems.